Răspuns :
Răspuns:
Explicație pas cu pas:
[((4x + 6 ) : 3 + 20 ] × 3 - 50 = 40
[( 4x + 6 ) : 3 + 20 ] × 3 = 40 + 50
[( 4x + 6 ) : 3 + 20 ] × 3 = 90
(4x + 6 ) : 3 + 20 = 90 : 3
(4x + 6 ) : 3 + 20 = 30
(4x + 6 ) : 3 = 30 - 20
(4x + 6 ) : 3 = 10
4x + 6 = 10 × 3
4x+ 6 = 30
4x = 30 - 6
4x = 24
x = 24 : 4
x = 6
[ ( 4 x + 6 ) : 3 + 20 ] × 3 - 50 = 40
[ ( 4 x + 6 ) : 3 + 20 ] × 3 = 40 + 50
[ ( 4 x + 6 ) : 3 + 20 ] × 3 = 90
( 4 x + 6 ) : 3 + 20 = 90 : 3
( 4 x + 6 ) : 3 + 20 = 30
( 4 x + 6 ) : 3 = 30 - 20
( 4 x + 6 ) : 3 = 10
4 x + 6 = 10 × 3
4 x + 6 = 30
4 x = 30 - 6
4 x = 24
x = 24 : 4
x = 6